The Effectiveness of Addition of Tapioca Flour in Artificial Feed on The Growth of Koi Carp (Cyprinus rubrofuscus) - Adzkiyah, Salsabillah Nur; Umami, Muhimatul (Universitas Sembilanbelas November Kolaka, 2021)
Growth is the process of increasing the number of cell protoplasm in an organism accompanied by an increase in size, weight and number of cells that cannot return to their previous state. One of the factors that influence the growth of koi carp is feed. Good feed is feed that can meet the nutritional needs of the koi carp. The addition of tapioca flour in the feed formula, which contains artificial feed, tapioca flour, and water in the koi carp feed, is one of the proper steps because of the increase in carbohydrate doses that can support the growth of the koi carp. This study aims to determine the benefits of adding tapioca flour to the artificial feed of the koi carp (Cyprinus rubrofuscus) and to determine the effect and the most appropriate dose of adding tapioca flour to the artificial diet of the koi carp (Cyprinus rubrofuscus). The research method used is a quantitative research method accompanied by direct observation and analysis of research data, which is also accompanied by a literature study method from previous studies to support the findings in the research results. The results showed thatÂ the more feed formula was given, the faster the growth of the koi carp produced. But must be accompanied by the right dose, which is 8 grams of feed formula once a day. While the benefits of adding tapioca flour in carp feed are increasing carp production, prolonging goldfish life expectancy, increasing efficiency and nutritional content in carp feed, increasing carp appetite accompanied by increased growth.Â Keywords: Goldfish Koi, Growth, Feed, Carbohydrates, Tapioca Starch